Budidaya Rumput Laut Eucheuma spinosum Di Pantai Muluk Gerupuk Kabupaten Lombok Tengah - Nuryatin; Pilo; M. Zohri; Cokrowati, Nunik; Lumbessy, Salnida Yuniarti; Wahyuningsih, Endah; Faris, Muhammad; Agustina, Dwi; Suhendri, Salwa; Sa’ban, Muhammad Iman Nichfu; Irfani, Febriana (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Eucheuma spinosum is a seaweed included in the red algae (Rhodophyta). The content of compounds in seaweed as secondary metabolites functions as antioxidants, antivirals, antifungals and antimicrobials in brown, red and green seaweed. Eucheuma spinosum is one type of red seaweed that has the potential as an antimicrobial compound due to the presence of bioactive components consisting of saponins and flavonoids. The purpose of this activity is applying seaweed cultivation using bottom off method. The activity was carried out at Muluk Beach, Gerupuk, Sengkol Village, Pujut District, Central Lombok Regency. Activities were carried out for 30 days, from July 28, 2024 to August 26, 2024. The method of implementing the activity is a demonstration plot of Eucheuma spinosum cultivation. Therefore, this activity was carried out to increase the production of Eucheuma spinosum seaweed in Gerupuk. The results of this activity are Eucheuma spinosum cultivation used bottom off method.